Knowledge, attitude, and practice of beef providers and consumers regarding microbial safety measures along the supply chain in Mizan-Aman, southwest Ethiopia - Girma Mamo Zegene; Seblework Mekonen Shegen; Seid Tiku Mereta (Heliyon)
Background: Beef meat is the widely consumed, and offers diverse nutritional value, despite health risks due to unsafe handling throughout the supply chain. Majority of existing researches have been primarily focus on beef handlers’ microbial safety status at single level, rather than addressing the potential contamination factors in the supply chain. In this study both beef providers and consumers microbial safety status was assessed and will contribute evidences in public health protection strategies. Methods: A cross-sectional study was carried out among randomly selected beef retailers' owners, managers (n = 44) and systematically selected beef consumers (n = 422). The data were collected using semi-structured questionnaires and structured observation checklist between February 20th and April 20th, 2024. Descriptive statistics and logistic regression were carried out to summarize the sociodemographic characteristics, and identify associated factors with participants’ microbial safety status. Candidate sociodemographic characteristics with a p-value of ≤0.25 in univariate analysis were included in the multivariable logistic regression using AOR 95 % CI and set a statistical significance at p < 0.05. Results: Majority of beef retailers' owners had poor knowledge (65.6 %), unfavorable attitude (65.4 %), and poor practices (78.6 %). Similarly, beef consumers had poor knowledge (64 %), unfavorable attitude (65 %), and poor practices (56 %) toward microbial safety measures. Furthermore, beef retailers’ owners and managers who completed high school were seven times more likely to have good knowledge [AOR = 7.02, 95 % CI: 1.11–2.47] compared to individuals who did not read and write. Likewise, beef consumers who had completed college and above were four times more likely to possess good knowledge concerning microbial safety activities [AOR = 4.00, 95 % CI: 1.09–14.79] than who were unable to read and write. Conclusion: Findings highlight a critical need for enhanced education and training programs regarding microbial safety measures for both of beef providers and consumers.